Komposisi Spesies Hasil Tangkapan Alat Tangkap Rawai Dasar yang Didaratkan di Pelabuhan Perikanan Nusantara (PPN) Brondong - M Yusril Izzah Maulana; Achmad Kusyairi; Alif Astagia (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The study aims to determine the species of fish caught by bottom longline and the composition of the number of fish species. The implementation time was carried out on December 11, 2024 - January 11, 2025 at Brondong Port, Lamongan Regency. The method used in this study is the method eksperimental fishing by conducting direct observation of the catch of bottom longline fishing gear. then conducting direct observation of the number of tails and weight of the catch and conducting direct interviews with bottom longline fishermen who operate their longline fishing gear in the waters of Brondong. The results of the bottom longline catch during the research at PPN Brondong which was landed in December 2024, there were 4 types of species caught by the bottom longline fishing gear, namely the swordtail shark ( rhizoprionodon acutus), Manyung Fish (arius thalassinus), Flower Ray (Taeniura lymma) and Remang (congresox talabonoides).